2013
DOI: 10.1371/journal.pone.0065664
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Hair Follicle Development in Engineered Skin Substitutes

Abstract: Generation of skin appendages in engineered skin substitutes has been limited by lack of trichogenic potency in cultured postnatal cells. To investigate the feasibility and the limitation of hair regeneration, engineered skin substitutes were prepared with chimeric populations of cultured human keratinocytes from neonatal foreskins and cultured murine dermal papilla cells from adult GFP transgenic mice and grafted orthotopically to full-thickness wounds on athymic mice. Non-cultured dissociated neonatal murine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 35 publications
1
27
0
1
Order By: Relevance
“…The first group (scaffolds seeded with chimeric cells) formed hairs without sebaceous glands, while the third group (scaffolds with human-only cells) formed no follicles or glands. The study showed that sebaceous glands are not required for hair formation when using this protocol (Sriwiriyanont et al 2013).…”
Section: Synthesis Of Hair Follicles and Sebaceous Glandsmentioning
confidence: 87%
“…The first group (scaffolds seeded with chimeric cells) formed hairs without sebaceous glands, while the third group (scaffolds with human-only cells) formed no follicles or glands. The study showed that sebaceous glands are not required for hair formation when using this protocol (Sriwiriyanont et al 2013).…”
Section: Synthesis Of Hair Follicles and Sebaceous Glandsmentioning
confidence: 87%
“…The creation of hair follicles has recently been successfully completed in skin substitutes, although the methodology behind it is lengthy and tedious[156,157]. Although it may take time for hair follicles stem cells to be incorporated into clinically available skin substitutes, there is hope that at least in vitro trichogenesis is now possible.…”
Section: Components Of a Skin Substitutementioning
confidence: 99%
“…The Lef1, a member of the WNT pathway, is a spe cific marker of early regeneration and development processes of the HF (Sriwiriyanont et al, 2013). We did not observe Lef1 expression in coated aggregates (Fig.…”
Section: Dermal Papilla Inhibits Proliferation Of Keratinocytesmentioning
confidence: 74%